Novel electrospun poly-hydroxybutyrate scaffolds as carriers for the wound healing agents alkannins and shikonins. Issue 3 (10th June 2021) - Arampatzis, Athanasios S; Giannakoula, Konstantina; Kontogiannopoulos, Konstantinos N; Theodoridis, Konstantinos; Aggelidou, Eleni; Rat, Angélique; Kampasakali, Elli; Willems, Anne; Christofilos, Dimitrios; Kritis, Aristeidis; Papageorgiou, Vassilios P; Tsivintzelis, Ioannis; et al.
Abstract: The aim of this study was to investigate the potential of novel electrospun fiber mats loaded with alkannin and shikonin (A/S) derivatives, using as carrier a highly biocompatible, bio-derived, eco-friendly polymer such as poly[(R)-3-hydroxybutyric acid] (PHB). PHB fibers containing a mixture of A/S derivatives at different ratios were successfully fabricated via electrospinning. Αs evidenced by scanning electron microscopy, the fibers formed a bead-free mesh with average diameters from 1.25 to 1.47 μm. Spectroscopic measurements suggest that electrospinning marginally increases the amorphous content of the predominantly crystalline PHB in the fibers, while a significant drug amount lies near the fiber surface for samples of high total A/S content. All scaffolds displayed satisfactory characteristics, with the lower concentrations of A/S mixture-loaded PHB fiber mats achieving higher porosity, water uptake ratios, and entrapment efficiencies. The in vitro dissolution studies revealed that all samples released more than 70% of the encapsulated drug after 72 h. All PHB scaffolds tested by cell viability assay were proven non-toxic for Hs27 fibroblasts, with the 0.15 wt.% sample favoring cell attachment, spreading onto the scaffold surface, as well as cell proliferation. Finally, the antimicrobial activity of PHB meshes loaded with A/S mixture was documented for Staphylococcus epidermidis and S. aureus .